Homeoindex - Mesquita, A.; Martins, C.C.; Cepeda, L.M.R. (British Homeopathic Journal, 1994)
HOMEOINDEX is a bibliographic database in which everything published in the field of homoeopathy is progressively filed. The methods adopted are those used by major international medical databases (MEDLINE, LILACS), allowing data exchange.HOMEOINDEX radically changes the situation for dissemination, study, preservation and research of homoeopathic works. It takes homoeopathy out of an archaic phase when work was inaccessible and fragmented and into the modern era.The development of this work included some unique achievements:—Introduction of homoeopathy as recognized literature in international institutions—Adoption of homoeopathic terms (key-words) in official latin-American medical catalogues—Creation of a Latin American reference centre, for cataloguing and disseminating homoeopathic literature—The introduction of homoeopathic papers to international medical databases.
Keywords: Homeoindex; Bibliography; Database; References; Latin America; Brazil